Layered Gradient Rhombic Dodecahedron Composite Structures for Biomimetic Bone Fabricated via Selective Laser Melting - Yun Zhai; Tianyuan Zhong; Shuangquan Guo; Sheng Lin; David Hui; Xiaowei Ma (Micromachines, 2025)
Porous bone implants have been extensively studied, with gradient structures receiving increasing attention due to their superior compatibility with bone tissue. However, comparative studies between gradient and uniform structures remain relatively scarce. In this study, selective laser melting (SLM) technology was employed to fabricate a gradient composite Ti6Al4V humeral bone plate, utilizing rhombic dodecahedron and its derived structures as unit cells. By adjusting the porosity parameter range to 22.02–94.37% using the Ashby Gibson formula, the mechanical properties of the porous bone plate were analyzed by varying the porosity parameters and conducting compression tests. The experimental results show that after preparing and compressing the structure, the elastic modulus of the model is controlled between 0.09–5.43 GPa, and the maximum yield strength is 216.1 Mpa. The experimental results demonstrate that, under shear loading, the gradient structure generates stress from the center of mass, with the phenomenon becoming more pronounced as the number of struts aligned with the direction of the applied load increases. This results in the model exhibiting characteristics of good resilience on the outside and a certain degree of rigidity on the inside. Compared to non-gradient models, gradient structures are more effective in controlling the direction of force transmission. Moreover, the elastic modulus of the bone plate is closer to that of natural bone tissue. These findings provide valuable insights for further research into gradient structure models of other rod-shaped unit cells, highlighting the mechanical advantages of gradient structures over uniform ones.